Collective action and vulnerability: Local and migrant networks in Bukidnon, Philippines - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Belonging to a group is highly valued in Filipino society. Values supportive of harmonious relationships, and an individual's personal network of selected relatives and other allies, affect how Filipinos function in organizations. This study examines the role of groups and networks in helping the poor manage their exposure to risks and cope with shocks to their livelihoods. Two types of groups are considered: local formal groups and informal networks, and migrant networks composed of family members.